A look at the Rionegro Antioquia exports in the last three years - Duque - Castaño, Yeny Paola; Ceballos - Ramírez, Silvia Liliana; Lukau - Quintero, Claudia Elena (Universidad Francisco de Paula Santander, 2021)
The exportable supply is defined as the capacity of the productive units to adapt goods and services to the demand of the external market, where variables such as quality, continuous supply, financial and commercial capacity must be met. In this same concept, it should be noted that this is an analysis of the potential of a municipality, city, region, department or country, to determine the products that can be exported or if they are already exported, how they can enter other markets. In this regard, the economic policies of recent governments have sought to bet on the dynamism and growth of exports, with the purpose of implementing actions, strategies, programs and instruments that increase business productivity, as well as the quality and added value of exports products. Therefore, cities and regions must bet on the insertion of their economies in international markets. Rionegro, is positioned as an intermediate municipality in the altiplano area of the Oriente Antioqueño subregion, with outstanding processes in trade, economic growth, business settlement and logistics infrastructure that allows it to be connected with the main cities of the country and the world. In this article, an analysis of the incursion of the Rionegro companies in the external context, as well as products and target markets in the last three years, shows a great variety of products exported to more than seventy countries.